Physical Characterization of Micro-Porosity in Decellularized Gambier Leaf for Potential Use as a Plant-Based Scaffold - Adenina, Syarinta; Ar Rahmat, Muhammad Firdzi; Mozartha, Martha; K, Trisnawaty; Tamzil, Nia Savitri; Adnindya, Msy Rulan; Hanifah, Masayu Nabila; Alfajri, Fariz (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2026)
Background: Scaffolds represent biomaterials designed to provide structural support for cellular adhesion and growth factor sequestration, emulating the extracellular matrix (ECM) to promote tissue regeneration. Plant-based tissues have garnered attention as viable scaffold alternatives owing to their architectural homology with human extracellular structures. Gambier leaves (Uncaria gambir) stand out for their inherent porous, trabecular morphology, where microporosity is pivotal in facilitating cell attachment, proliferation, and differentiation. Objective: This study aims to elucidate the microporous characteristics of decellularized gambier leaves via scanning electron microscopy (SEM). Method: Fresh leaves were meticulously cleaned, cryopreserved at −20°C, and fashioned into five circular discs employing a biopsy punch. Decellularization entailed submersion in 10% sodium dodecyl sulfate (SDS) for five days, succeeded by distilled water lavage. Subsequent cyclic treatment with Tween-20 and NaClO solutions, applied every 24 hours, continued until optical translucency was achieved. Processed tissues underwent thorough washing, overnight fixation, serial ethanol dehydration, hexamethyldisilazane (HMDS) treatment, 50 nm gold sputter-coating, and SEM evaluation across three magnifications. Results: Microscopy revealed surface wrinkling and partial architectural collapse in multiple specimens, likely due to dehydration-induced artifacts. Conversely, a single intact sample exhibited pronounced microporosity, as evidenced by pore diameters of 0.689 µm and 0.5512 µm. Conclusion: These observations affirm the microporous potential of decellularized gambier leaves for cellular anchorage and nutrient permeation, bolstering their candidacy as plant-derived scaffolds in tissue engineering. Nonetheless, inter-sample variability underscores the need for refined decellularization/dehydration methods and expanded quantitative assessments to ensure reproducible structural integrity.